2021
DOI: 10.1021/acs.jafc.1c03105
|View full text |Cite
|
Sign up to set email alerts
|

Regulation on Citrate Influx and Metabolism through Inhibiting SLC13A5 and ACLY: A Novel Mechanism Mediating the Therapeutic Effects of Curcumin on NAFLD

Abstract: Upregulated de novo lipogenesis (DNL) plays a pivotal role in the progress of the nonalcoholic fatty liver disease (NAFLD). Cytoplasmic citrate flux, mediated by plasma membrane citrate transporter (SLC13A5), mitochondrial citrate carrier (SLC25A1), and ATP-dependent citrate lyase (ACLY), determines the central carbon source for acetyl-CoA required in DNL. Curcumin, a widely accepted dietary polyphenol, can attenuate lipid accumulation in NAFLD. Here, we first investigated the lipidlowering effect of curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It also inhibits HMGB1-NF-κB translocation, macrophage M1 polarization, and inflammatory factor secretion to reduce liver damage. Cur can alleviate NASH by upregulating the Nrf2 gene, protecting mitochondria, and reducing apoptosis. , Additionally, Cur improves hepatic lipid accumulation to curb NASH development through the AMPK-mTOR signaling pathway . THC is reported to protect against NAFLD by reducing adipogenesis, activating AMP-activated protein kinase, and increasing fatty acid oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits HMGB1-NF-κB translocation, macrophage M1 polarization, and inflammatory factor secretion to reduce liver damage. Cur can alleviate NASH by upregulating the Nrf2 gene, protecting mitochondria, and reducing apoptosis. , Additionally, Cur improves hepatic lipid accumulation to curb NASH development through the AMPK-mTOR signaling pathway . THC is reported to protect against NAFLD by reducing adipogenesis, activating AMP-activated protein kinase, and increasing fatty acid oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting multiple metabolic pathways may be a more effective strategy. Our group previously reported that curcumin, a natural product, regulates hepatocyte citrate flux by directly inhibiting the function of SLC13A5 and ACLY and indirectly regulating the expression of SLC13A5 and ACLY by activating the AMPK–mTOR signaling pathway to treat hyperlipidemia . Several studies have found that a compensatory increase in acetate occurs when the source of citrate was reduced. , Acetyl-CoA synthetase 2 (ACSS2) can convert acetate to acetyl-CoA and supplement the carbon source required for lipid synthesis under certain conditions .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Curcumin has significant lipid lowering effect and inhibit the overexpression of SLC13A5 and ACLY. This further reduces the upregulation of de novo lipogenesis and regulates the lipid accumulation in NAFLD in mice [64]. The hydroxy citric acid extract from the Garcinia cambogia was evaluated for the inflammatory, atherogenic and metabolic biomarkers in 40 obese women with NAFLD.…”
Section: Role Of Citrate In Fatty Liver Diseasementioning
confidence: 99%